2019
DOI: 10.20471/acc.2019.58.s1.07
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anaesthesia for Neurosurgery

Abstract: SummaryDuring neurosurgery procedures it is vital to assure optimal cerebral perfusion and oxygenation. Despite physiological autoregulation of brain perfusion, maintaining hemodynamic stability and good oxygenation during anesthesia is vital for success. General anesthesia with mechanical ventilation and current drugs provide excellent hemodynamic condition and it is the first choice for most neurosurgery procedures. However, sometimes it is very hard to avoid brief increase or decrease in blood pressure espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…10 Thus, landmark-based blind injections and blocks in this region are fraught with unintentional injury or blockade of the branches of the facial nerve or intravascular injections. 2,5,6 A recent cadaveric study has shown a high rate of staining of the frontotemporal and zygomatic branches of the facial nerve when 1 to 2 mL of methylene blue was used to simulate the blockade of the zygomaticotemporal nerve and auriculotemporal nerve using a traditional landmark-based technique. 13 Hence, we used a low volume of local anesthetics under real-time ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…10 Thus, landmark-based blind injections and blocks in this region are fraught with unintentional injury or blockade of the branches of the facial nerve or intravascular injections. 2,5,6 A recent cadaveric study has shown a high rate of staining of the frontotemporal and zygomatic branches of the facial nerve when 1 to 2 mL of methylene blue was used to simulate the blockade of the zygomaticotemporal nerve and auriculotemporal nerve using a traditional landmark-based technique. 13 Hence, we used a low volume of local anesthetics under real-time ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Use of regional anaesthesia using neuraxial blockade in the subarachnoid, epidural, and combined subarachnoid epidural planes is increasingly preferred over general anaesthesia (GA) for lumbar microsurgical procedures. [ 19 ] Likewise, ultrasound-guided cervical plexus blocks (superficial, intermediate, and deep) for anterior cervical discectomy and fusions, brachial plexus blocks for carotid endarterectomy, erector spinae, and paravertebral blocks for cervical/thoracic/lumbar surgeries and iliac crest bone graft harvest are increasingly being used to circumvent the morbidity associated with GA. Additionally, non-GA scenarios permit live neurofeedback that aids the surgeons in gauging their proximity to critical neural structures, reducing the risk of neuronal injury.…”
Section: A) Newer Advancements In Neuroanaesthesiamentioning
confidence: 99%
“…2 Dengan tersedianya obat anestesi lokal yang mempunyai lama kerja panjang, serta perkembangan dari teknik scalp block sendiri dari yang semula memblok area insisi operasi pada kulit kepala dengan infiltrasi anestesi lokal, menjadi teknik lebih selektif yaitu dengan memblok serabut saraf yang mempersarafi area insisi pada kulit kepala, hal ini membuka kesempatan yang lebih luas dalam penggunaan teknik Scalp block ini. [1][2][3]…”
Section: Pendahuluanunclassified
“…2,4 Kontraindikasi Kontraindikasi penggunaan teknik scalp block ini sangat jarang, namun bagi individu yang alergi terhadap anestesi lokal teknik ini dikontraindikasikan demikian juga untuk dihindari injeksi anestesi lokal pada daerah yang mengalami infeksi. 3,4…”
Section: Indikasi Dan Kontra Indikasiunclassified